Analysis of Respiratory Tract Cancer: A Population-Based Study - Ferreira, Pedro M. P.; Turcatto, Isabela M.; Takahashi, André A. R.; Paiva, Laércio S.; Sousa, Luiz Vinícius A. (European Scientific Journal, ESJ, 2021)
Cancer is one of the main causes of mortality in Brazil and in the world. Respiratory cancer is one of the most expressive fractions. It is important to study its incidence and try to correlate its association with behavioral factors in big urban centers such as the ABC region in Sao Paulo. This paper focuses on analyzing and comparing the incidence of respiratory tract cancers in the population of the ABC region and their respective correlations with the state of Sao Paulo and Southeast region. This is an ecological observational study with temporal analysis, using secondary data referring to hospital admissions for cancer of the larynx, trachea, and lung in the ABC region from 2008 to 2017. In the ABC region, the female sex showed a greater increase in older age groups. Sao Paulo showed a significant increase for both genders in the age group over 60 years old. Southeast region showed the greatest significant variation, with the male gender decreasing in the younger age groups and increasing in the older age groups, while the female is increasing in older age groups. Airway cancers in the younger age groups for both males and females are decreasing in all regions analyzed. For older age groups, numbers are increasing especially in the ABC region. The most important correlation found in this study is an increase in the number of cases of these diseases in women compared to men, which may suggest that females have increased their tobacco consumption, while men appear to be decreasing.